La-Fe-Si-based magnetic refrigeration composite material and preparation method thereof

By adopting a layered structure design in La(Fe,Si)13-based magnetic refrigeration material, the combination of pores and magnetothermal phase units and the alternating lamination of Fe or Fe alloys, the problem of insufficient material brittleness and thermal conductivity is solved, and the combination of large magneto-thermal effect and strong anisotropic thermal conductivity is achieved, ensuring the shape integrity after hydrogen filling.

CN119560250AActive Publication Date: 2025-03-04NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311140593.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-04
Publication Date
2025-03-04
Estimated Expiration
2043-09-04

AI Technical Summary

Technical Problem

The existing La(Fe,Si)13-based magnetic refrigeration material has high brittleness, and the crystal lattice expansion after hydrogen absorption leads to breakage. Its microstructure and properties are isotropic, making it difficult to achieve strong anisotropic thermal conductivity.

Method used

A layered structure is adopted which is alternately laminated by the first composition layer and the second composition layer. The first composition layer includes a pore and a plurality of magnetothermal phase units. The second composition layer includes Fe or Fe alloy. After pressing and molding the cast La-Fe-Si-based alloy powder and Fe, Si and other powders, the magnetothermal phase is obtained to form a La(Fe,Si)13-based compound with a NaZn13 crystal structure.

Benefits of technology

It realizes the large magneto-thermal effect and strong anisotropic thermal conductivity of La-Fe-Si-based magnetic refrigeration composite material, while ensuring the complete shape after hydrogen filling, and is suitable for the design and manufacturing of high-performance magnetic refrigeration systems.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119560250A_ABST
    Figure CN119560250A_ABST
Patent Text Reader

Abstract

The invention relates to a La-Fe-Si-based magnetic refrigeration composite material and a preparation method thereof.The La-Fe-Si-based magnetic refrigeration composite material is of a layered structure formed by pressing a first composition layer and a second composition layer after the first composition layer and the second composition layer are alternately stacked, the first composition layer comprises pores and a plurality of magnetocaloric phase units, the second composition layer comprises Fe or Fe alloy, and the magnetocaloric phase is La (Fe, Si) with a NaZn13 type crystal structure. Si) 13-group compounds. After the La-Fe-Si-based magnetic refrigeration composite material is subjected to high-temperature reaction, all the magnetic thermal phase units in the first composition layer are connected with one another to form an integrated structure; thus, when the La-Fe-Si-based alloy layer is inflated with hydrogen and expands, the pores play a buffering role, the situation that crystalline grains are crushed due to extrusion of crystalline grain phases is avoided, and the overall volume change of the La-Fe-Si-based alloy layer is reduced; fe or Fe alloy particles are compact, are still of a continuous layered structure and are tightly connected with the La-Fe-Si-based alloy layer, so that the obtained layered structure plays a role in inhibiting mutual separation of layers of the composite material caused by hydrogen charging, and the layered composite material after hydrogen charging basically keeps the original shape and is not broken.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a magnetic refrigeration material, in particular to a La-Fe-Si based magnetic refrigeration composite material, belonging to the field of magnetic refrigeration materials. Background Art

[0002] Traditional gas compression refrigeration technology generally has many problems such as low efficiency, high energy consumption, and high greenhouse gas emissions. Magnetic refrigeration, as a high-efficiency, energy-saving, and environmentally friendly refrigeration technology, has attracted widespread attention and has become one of the most promising methods to replace traditional gas compression refrigeration. Compared with traditional gas compression refrigeration, the advantages of magnetic refrigeration are: (1) high refrigeration efficiency, with a COP value of more than 16, while the COP of gas compression refrigeration is less than 5; (2) low energy consumption, saving 30% energy compared to traditional refrigeration; (3) no greenhouse gas emissions, environmentally friendly; (4) low noise, high reliability, and easy maintenance.

[0003] The working principle of magnetic refrigeration is mainly based on the magnetocaloric effect of magnetic materials. Early research in this field focused on improving the magnetocaloric effect of materials and related magnetic properties. Since 1997, materials with room temperature giant magnetocaloric effect have been discovered, including Gd5(Si,Ge)4-based alloys, MnAs-based alloys, MnFe(P,As,Si,Ge)-based alloys, La(Fe,Si) 13 Base alloys and Heusler alloys. Among these materials, NaZn 13 La(Fe,Si) type crystal structure 13 The base alloy has high entropy change, adiabatic temperature change and low hysteresis, and the Curie temperature of the alloy can be adjusted to room temperature by element doping and substitution. More importantly, this type of alloy is recognized as one of the most likely materials to be widely used in magnetic refrigerators because of its advantages such as abundant raw materials (La is a high-abundance rare earth element), low cost and non-toxic elements. Studies have shown that hydrogenation treatment is an effective means for this type of material to simultaneously obtain a large magnetocaloric effect and a near-room temperature operating temperature. However, La(Fe,Si) 13 The brittleness of the compound is very large. After the introduction of interstitial H atoms, the lattice will expand violently, thus initiating cracks, causing the bulk alloy to break severely or even turn into powder. On the other hand, the current magnetic refrigeration technology generally adopts an active heat recovery mode. This heat recovery mode requires that the magnetic refrigerant can quickly and fully exchange heat with the heat exchange fluid to improve the working efficiency of the magnetic refrigeration system. To this end, it is necessary to process the magnetic refrigeration material into a geometric shape with a large specific surface area (such as thin sheets, spheres), and improve the thermal conductivity of the material itself. A more ideal design is to increase the thermal conductivity of the magnetic refrigerant perpendicular to the direction of the heat exchange fluid, while reducing the thermal conductivity along the direction of the fluid, that is, to achieve strong anisotropic thermal conductivity of the magnetic refrigerant.

[0004] The La(Fe,Si) 13 Most of the microstructures and properties of the basic magnetic refrigeration materials are isotropic. For example, the Chinese invention patent "Bonded La(FeSi) 13 Based on magnetocaloric effect materials and their preparation methods and uses, the patent number of which is ZL201110374158.1 (the authorization announcement number is CN103137281B) discloses a bonded La(FeSi) 13 Based on magnetocaloric effect materials, the adhesive bonding thermosetting molding method is adopted. By adjusting the molding pressure, thermosetting temperature, thermosetting atmosphere, etc., high-strength bonding La(Fe,Si) 13 The magnetocaloric effect material overcomes the inherent brittleness of the magnetocaloric effect material; the magnetic entropy change can remain basically unchanged compared with that before bonding, but the thermal conductivity of the polymer adhesive is poor, resulting in very low thermal conductivity in all directions of the composite material. In the rare earth-iron-silicon-based magnetic refrigeration composite material disclosed in the Chinese invention patent "A rare earth-iron-silicon-based magnetic refrigeration composite material and its preparation method" previously applied by the applicant, its patent number is ZL201710849594.7 (authorization announcement number is CN109524190B), low-density, high-thermal conductivity aluminum metal or aluminum alloy is used as a matrix component and mixed with rare earth-iron-silicon-based alloy particles and then hot-pressed to obtain a block of magnetic refrigeration composite material, aluminum metal or aluminum alloy is used as the second component to bond the rare earth-iron-silicon-based alloy particles, and the two matrix components are easy to overlap each other to form a mesh structure, so that the thermal conductivity and mechanical properties are significantly enhanced, but the thermal conductivity in all directions is the same. In recent years, in order to further improve the heat exchange efficiency of magnetic regenerators and reduce the internal heat loss of magnetic working fluids, researchers in this field have gradually developed La(Fe,Si) 13 Based on magnetocaloric effect materials. For example, in the non-patent literature (Acta Materialia 2020, 187, 1), a room temperature free forging method is used to deform the cast La-Fe-Si alloy, and then anneal it to prepare a fully dense La(Fe,Si) 13 / Fe thin-sheet composite material, the Fe inside the material is in lamellar form, and the difference in room temperature thermal conductivity in the direction perpendicular to and parallel to the applied pressure is about 1.5W / mK, which is far from the ideal value. In order to obtain good comprehensive performance, La(Fe,Si) 13 The basic magnetic refrigeration material needs to rely on the second phase to enhance the mechanical and thermal conductivity. When absorbing hydrogen, the La(Fe,Si) 13 The lattice will expand isotropically, while the volume of the second phase often remains unchanged. For composite materials with macroscopic anisotropic structures, large stresses are easily generated between the magnetocaloric phase and the second phase, which in turn causes the two phases to separate, making it difficult to form a complete bulk material.

[0005] To this end, it is necessary to further improve the existing La-Fe-Si based magnetic refrigeration materials to obtain bulk materials that have both large magnetocaloric effect near room temperature and strong anisotropic thermal conductivity to meet the requirements of designing and manufacturing high-performance magnetic refrigeration systems. Summary of the invention

[0006] The first technical problem to be solved by the present invention is to provide a La-Fe-Si based magnetic refrigeration composite material with a large magnetocaloric effect and strong anisotropic thermal conductivity, while ensuring the integrity of the shape after hydrogen filling, in view of the current status of the above-mentioned prior art.

[0007] The second technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned La-Fe-Si based magnetic refrigeration composite material.

[0008] The technical solution adopted by the present invention to solve the above-mentioned first technical problem is: a La-Fe-Si based magnetic refrigeration composite material, characterized in that the La-Fe-Si based magnetic refrigeration composite material is a layered structure formed by alternating a first component layer and a second component layer, the first component layer comprises pores and a plurality of magnetocaloric phase units, each magnetocaloric phase is interconnected to form an integral structure, the second component layer comprises Fe or Fe alloy, the magnetocaloric phase is a layer having NaZn 13 La(Fe,Si) type crystal structure 13 Base compound.

[0009] The second component layer is a tough layer, and its thermal conductivity is higher than that of the first component layer.

[0010] The NaZn 13 La(Fe,Si) type crystal structure 13 The chemical formula of the base compound is: La 1-x R x (Fe 1-a M a ) 13- y Si y A z ; wherein R is selected from any one or a combination of two or more of Ce, Pr and Nd elements; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni and Al elements; A is H element; or, A is selected from one or a combination of two or more of B and C elements and H; 0≤x≤0.5, 1≤y≤2, 0≤z≤0.5, 0≤a≤0.1.

[0011] In the La-Fe-Si-based magnetic refrigeration composite material, by mass percentage, the content e of the first component layer in the La-Fe-Si-based magnetic refrigeration composite material satisfies: 60 wt.% < e < 100 wt.%, and the content f of the second component layer in the La-Fe-Si-based magnetic refrigeration composite material satisfies: 0 < f < 40 wt.%. In the La-Fe-Si-based magnetic refrigeration composite material of the present invention, the first component layer contains La(Fe,Si) 13 Based compounds are the source of the magnetocaloric effect. The second component layer serves as a high thermal conductivity channel and is the source of anisotropic thermal conductivity, but does not produce a magnetocaloric effect. To balance the magnetocaloric and thermal conductivity properties of the composite material, the proportion contents of the two layers need to be strictly limited, and the sum of the contents of the two layers is 100 wt.%.

[0012] Preferably, the content f satisfies: 10 wt.% ≤ f ≤ 20 wt.%.

[0013] If the first component layer further includes a non-magnetocaloric phase, then the first component layer consists only of La(Fe,Si) 13 Based magnetocaloric phase, pores, and non-magnetocaloric phase. By volume percentage, the content g of the magnetocaloric phase in the first component layer satisfies: 60 < g < 100 vol.%, the content h of the pores in the first component layer satisfies: 0 < h < 20 vol.%, and the content m of the non-magnetocaloric phase in the first component layer satisfies: 0 ≤ m < 20 vol.%. In the La-Fe-Si-based magnetic refrigeration composite material of the present invention, the magnetocaloric phase provides the magnetocaloric effect, while the pores and non-magnetocaloric phase can both eliminate part of the stress caused by the hydrogen absorption expansion of the magnetocaloric phase, hinder the crack propagation inside the first component layer, and inhibit the separation between the first component layer and the second component layer, ensuring the integrity of the geometric shape of the composite material after hydrogen absorption. However, if the pores and non-magnetocaloric phase are too much, it will inevitably lead to a serious reduction in the magnetocaloric performance of the composite material. Therefore, it is necessary to strictly limit the proportion contents of each component phase in the first component layer.

[0014] The La-Fe-Si-based magnetic refrigeration composite material has a Curie temperature range of 150 K to 350 K, and the entropy change value under a magnetic field change of 2 T is not less than 8 J / kgK, so the La-Fe-Si-based magnetic refrigeration composite material has a large magnetocaloric effect near room temperature.

[0015] For the La-Fe-Si-based magnetic refrigeration composite material, denote the stacking direction of the layered structure as the first direction, and the direction perpendicular to the first direction as the second direction. The difference Δλ between the thermal conductivity λ1 of the La-Fe-Si-based magnetic refrigeration composite material along the first direction and the thermal conductivity λ2 along the second direction satisfies: Δλ ≥ 2 W / mK.

[0016] The La-Fe-Si based magnetic refrigeration composite material can be processed into a thickness of less than 2 mm and a cross-sectional area of ​​not less than 100 mm. 2 After the plate-like material is filled with hydrogen, it can maintain its original shape without breaking.

[0017] The above cross-sectional area is the product of length and width.

[0018] The technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing the La-Fe-Si based magnetic refrigeration composite material, characterized in that it includes the following steps in sequence:

[0019] 1) According to the chemical formula La 1-x R x (Fe 1-a M a ) (13-y)b Si y A z Configure raw materials; wherein R is selected from any one or a combination of two or more of Ce, Pr and Nd elements; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni and Al elements; A is selected from one or a combination of two or more of B and C elements; 0≤x≤0.5, 1≤y≤2, 0.1≤z≤3, 0≤a≤0.1, 0.5≤b≤1.5;

[0020] 2) Smelting the raw materials prepared in step 1) to form La 1-x R x (Fe 1-a M a ) (13-y)b Si y A z alloy;

[0021] 3) La smelted in step 2) 1-x R x (Fe 1-a M a ) (13-y)b Si y A z The alloy is crushed into powder;

[0022] 4) The La crushed in step 3) 1-x R x (Fe 1-a M a ) (13-y)b Si y A zAlloy powder is used as a first component layer, and is alternately laid flat with Fe or Fe alloy powder as a second component layer, and then pressed into a green body after being laid flat, wherein the Fe alloy powder is a binary or multi-component alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si elements;

[0023] 5) annealing the compacted body in step 4) to obtain NaZn 13 Phase of type crystal structure;

[0024] 6) The green body after annealing in step 5) is subjected to hydrogen charging treatment to form a La-Fe-Si based room temperature magnetic refrigeration composite material.

[0025] Preferably, in step 4), the pressing is performed in a high vacuum environment or in an inert atmosphere, and if the pressing temperature is room temperature, the pressing pressure is 0.5 to 1.5 GPa. The heat treatment in step 5) is performed at a temperature of 1000 to 1200° C. for 5 to 72 hours.

[0026] In the process of implementing the present invention, it is found that the thermal conductivity in the first direction and the second direction are inversely proportional to the total thickness of the first component layer and the second component layer. The pore characteristics in the first component layer are related to the powder particle size. The smaller the particle size of the powder, the smaller the pore size and the greater the number. The integrity of the composite material is higher after hydrogen charging. Therefore, the sum of the thickness of the first component layer and the second component layer is less than 5mm, and the particle size of the powder of the first component layer is less than 300μm.

[0027] Another technical solution adopted by the present invention to solve the above second technical problem is: a method for preparing the La-Fe-Si based magnetic refrigeration material, characterized in that it comprises the following steps in sequence:

[0028] 1) According to R x Fe 13-y Si y The raw material is configured by chemical formula; wherein R is La; or, R is selected from any one or a combination of two or more of Ce, Pr, Nd and La, and x satisfies: 1≤x≤7, and y satisfies: 1≤y≤10;

[0029] 2) The raw materials prepared in step 1) are melted to form an alloy, and then R x Fe 13-y Si y The alloy is crushed into powder;

[0030] 3) The R broken in step 2) x Fe 13-y Si y Alloy powder is used as an intermediate, and mixed with Fe powder and Si powder; or, mixed with Fe powder, Si powder and alloy powder according to R x(Fe 1-a M a ) (13-y)b Si y A z The mixed powder is prepared according to the chemical formula, wherein the alloy powder is a binary or multi-element alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si; R is La; or, R is selected from any one or a combination of two or more of Ce, Pr, and Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, and Al elements; A is selected from one or a combination of two of B and C, x satisfies: 0.8≤x≤1.2, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, and b satisfies: 0.5≤b≤1.5;

[0031] 4) Mix the R mixed in step 3) x (Fe 1-a M a ) (13-y)b Si y A z Alloy powder is used as a first component layer, and is alternately laid flat with Fe or Fe alloy powder as a second component layer, and then pressed into a green body after being laid flat, wherein the Fe alloy powder is a binary or multi-component alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si elements;

[0032] 5) annealing the compacted body in step 4) to obtain NaZn 13 Phase of type crystal structure;

[0033] 6) The green body after annealing in step 5) is subjected to hydrogen charging treatment to form a La-Fe-Si based room temperature magnetic refrigeration composite material.

[0034] Preferably, in step 4), the pressing is performed in a high vacuum environment or in an inert atmosphere, and if the pressing temperature is room temperature, the pressing pressure is 0.5 to 1.5 GPa. The heat treatment in step 5) is performed at a temperature of 1000 to 1200° C. for 5 to 72 hours.

[0035] Compared with the prior art, the advantages of the present invention are: the La-Fe-Si-based magnetic refrigeration composite material is a layered structure formed by alternately stacking a first component layer and a second component layer and then pressing, the first component layer is a La-Fe-Si-based alloy layer, and the second component layer contains Fe or Fe alloy. After high-temperature reaction, the La-Fe-Si-based alloy layer (i.e., the first component layer) includes a magnetocaloric phase and pores, and each of the magnetocaloric phase units is interconnected to form an integrated structure; in this way, when hydrogen is charged and expanded, the pores play a buffering role, avoiding the crushing of grains and grain phases due to extrusion, and reducing the overall volume change of the La-Fe-Si-based alloy layer; and because the Fe or Fe alloy particles are dense and still a continuous layered structure, and are closely connected to the La-Fe-Si-based alloy layer, the layered structure obtained by the present invention inhibits the separation of the composite layers caused by hydrogen charging, and the layered composite material after hydrogen charging basically maintains its original shape without breaking.

[0036] The prior art usually gives priority to obtaining a magnetocaloric phase with a magnetocaloric effect and then presses it into shape. Pressure and temperature inevitably damage the magnetocaloric phase, resulting in a serious reduction in the magnetocaloric effect. The present invention avoids the above-mentioned destructive effect by pressing the cast La-Fe-Si-based alloy powder with Fe, Si and other powders and then obtaining the magnetocaloric phase. Therefore, the obtained La-Fe-Si-based magnetic refrigeration composite material has a large near-room temperature magnetocaloric effect. In addition, compared with the existing forging technology, the present invention adopts a molding technology to composite La-Fe-Si-based alloy and Fe or Fe alloy. By changing the thickness of the first component layer and the second component layer with high thermal conductivity, the proportion of the two layers, and the pressing pressure, the magnetocaloric effect and the thermal conductivity in different directions can be adjusted. Therefore, it is easier to achieve the stability and batch preparation of the composite layer structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] FIG. 1( a ) is a La in Example 1 of the present invention. 0.7 Ce 0.3 Fe 11.6 Si 1.4 Backscattering scanning electron microscopy image of / Fe magnetic refrigeration composite material;

[0038] Figure 1(b) is a La in Example 1 of the present invention 0.7 Ce 0.3 Fe 11.6 Si 1.4 A local magnified scanning electron microscope image of the first component layer of the / Fe magnetic refrigeration composite material;

[0039] FIG. 2( a ) is a diagram of La in Example 1 of the present invention. 0.7 Ce 0.3 Fe 11.6 Si 1.4Thermomagnetic (MT) curve of the Fe / Fe magnetic refrigeration composite material under a magnetic field of 0.05T;

[0040] Figure 2(b) is a diagram of La after hydrogenation in Example 1 of the present invention. 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z Thermomagnetic (MT) curve of the Fe / Fe magnetic refrigeration composite material under a magnetic field of 0.05T;

[0041] Figure 3 is the La after hydrogenation in Example 1 of the present invention 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z Isothermal magnetization (MH) curves of the / Fe magnetic refrigeration composite material during the field increase and field decrease at different temperatures;

[0042] Figure 4 is La after hydrogenation in Example 1 of the present invention 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z Curves of entropy change versus temperature of / Fe magnetic refrigeration composite materials under 1T and 2T magnetic fields;

[0043] Figure 5 is La after hydrogenation in Example 1 of the present invention 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z Curves of thermal conductivity of the Fe / Fe magnetic refrigeration composite material changing with temperature in the first direction and the second direction;

[0044] Figure 6 is La in Example 2 of the present invention 0.84 Ce 0.36 Fe 13.68 Si 1.6 Backscattering scanning electron microscopy image of / Fe magnetic refrigeration composite material;

[0045] Figure 7 is La after hydrogenation in Example 2 of the present invention 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z Thermomagnetic (MT) curve of the Fe / Fe magnetic refrigeration composite material under a magnetic field of 0.05T;

[0046] Figure 8 is La after hydrogenation in Example 2 of the present invention0.84 Ce 0.36 Fe 13.68 Si 1.6 H z Isothermal magnetization (MH) curves of the / Fe magnetic refrigeration composite material during the field increase and field decrease at different temperatures;

[0047] Fig. 9 is La after hydrogenation in Example 2 of the present invention 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z Entropy change curve of / Fe magnetic refrigeration composite material under 1T and 2T magnetic field changes. DETAILED DESCRIPTION

[0048] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be noted that in the following embodiments, the purity of the raw materials used is as follows: the purity of La, Ce, Fe, and Si is all above 99% (mass percentage content).

[0049] Embodiment 1:

[0050] The general chemical formula of the La-Fe-Si based magnetic refrigeration composite material of this embodiment is: La 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z / Fe.

[0051] Scanning electron microscope was used to observe the La 0.7 Ce 0.3 Fe 11.6 Si 1.4 The microstructure of the / Fe magnetic refrigeration composite material is shown in Figure 1 (a) and (b). The sample consists of a first component layer 1 and a second component layer 2, which are alternately stacked to form a layered structure. The first component layer 1 is composed of a magnetocaloric phase 11, pores 12 and a non-magnetocaloric phase 13, wherein the volume fraction of the pores is about 8.9%. The magnetocaloric phase 11 is NaZn 13 La(Fe,Si) type crystal structure 13 The non-magnetocaloric phase 13 is mainly composed of α-(Fe, Si) (black area) and La-Ce-rich rare earth phase (white area), of which the volume fraction of α-(Fe, Si) phase is about 9.7%. It can be seen that the fine non-magnetocaloric phase 13 is dispersed in the magnetocaloric phase 11. The second component layer 2 is mainly α-(Fe, Si) with a thickness of about 0.3 mm. The La-Ce-rich layer 13 is mainly composed of α-(Fe, Si) and α-(Si) phase.0.7 Ce 0.3 Fe 11.6 Si 1.4 / Fe magnetic refrigeration composite material still maintains its intact shape after being filled with hydrogen.

[0052] In this embodiment, La 0.7 Ce 0.3 Fe 11.6 Si 1.4 The preparation method of the / Fe magnetic refrigeration composite material comprises the following steps in sequence:

[0053] 1) Press La 0.7 Ce 0.3 Fe 11.6 Si 1.4 The chemical ingredients are loaded into the crucible of the vacuum induction rapid solidification furnace, and then filled with high-purity argon gas after evacuation. When the temperature rises to the point where the raw materials are completely melted and the alloy melt is uniform, the alloy liquid is poured onto a rotating copper roller to form an alloy sheet;

[0054] 2) La prepared in step 1) 0.7 Ce 0.3 Fe 11.6 Si 1.4 The alloy flakes are mechanically crushed into powder and sieved;

[0055] 3) The La with a particle size of 75 to 150 μm sieved in step 2) 0.7 Ce 0.3 Fe 11.6 Si 1.4 The alloy powder as the first component layer and the Fe powder with a particle size of 75 to 150 μm as the second component layer were alternately poured into the mold in a nitrogen glove box and laid flat; among them, La 0.7 Ce 0.3 Fe 11.6 Si 1.4 The mass of a single layer of powder is 1 g, and the mass of a single layer of Fe powder is 0.25 g. The layered powders are pressed into a green body at room temperature with a pressure of 1 GPa;

[0056] 4) La pressed in step 3) 0.7 Ce 0.3 Fe 11.6 Si 1.4 The / Fe blank is placed in a quartz tube, which is then evacuated, filled with argon, and sealed;

[0057] 5) Place the quartz tube containing the embryo in step 4) into an annealing furnace, heat to 1050°C, and anneal for 1 day to form a NaZn 13 La of magnetocaloric phase 0.7 Ce 0.3 Fe 11.6 Si 1.4 / Fe magnetic refrigeration composite material;

[0058] 6) La after annealing in step 5) 0.7 Ce 0.3 Fe 11.6 Si 1.4 The La / Fe composite material was charged to saturation in a hydrogen atmosphere at 300°C and 0.2 MPa to obtain 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z / Fe magnetic refrigeration composite materials.

[0059] Physical performance test:

[0060] 1. Determination of La obtained in step 5) and step 6) using superconducting quantum interference device vibrating sample magnetometer MPMS (SQUID) VSM 0.7 Ce 0.3 Fe 11.6 Si 1.4 / Fe and La after hydrogenation 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z / Fe magnetic refrigeration composite thermomagnetic (MT) curves, and La 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z Isothermal magnetization (MH) curves of the La / Fe magnetic refrigeration composite material at different temperatures. As can be seen from Figure 2 (a) and (b), 0.7 Ce 0.3 Fe 11.6 Si 1.4 The Curie temperature of the / Fe composite material is 170K, and the Curie temperature of the hydrogenated composite material increases to 315K. Figure 3 As shown in the figure, near the Curie temperature, the sample magnetization curve has an obvious inflection point, showing a first-order magnetic transition from paramagnetic to ferromagnetic state. According to Maxwell's relationship:

[0061]

[0062] The entropy change under different temperature and magnetic field changes is calculated from the isothermal magnetization curve. Figure 4 It can be seen that low magnetic field changes can cause a large entropy change in the layered composite material. The maximum entropy changes under 0-1T and 0-2T magnetic field changes are 12.1J / kgK and 14.9J / kgK, respectively.

[0063] 2. Use laser thermal conductivity analyzer (LFA) to test the La obtained in step 5).0.7 Ce 0.3 Fe 11.6 Si 1.4 / Fe layered composite material and the hydrogenated La obtained in step 6) 0.7 Ce 0.3 Fe 11.6 Si 1.4 H z Thermal conductivity of Fe / Fe layered composites. Figure 5 is the thermal conductivity of the composite material after hydrogenation at different temperatures. It can be seen that the composite material has obvious anisotropic thermal conductivity. At room temperature, the thermal conductivity of the sample in the first direction P1 and the second direction P2 before hydrogenation is 5.9W / mK and 11.9W / mK respectively, and the difference in thermal conductivity between the two directions is 6.0W / mK; the thermal conductivity of the sample decreases slightly after hydrogenation, and the thermal conductivity in the first direction and the second direction is 6.5W / mK and 8.5W / mK respectively, and the difference in thermal conductivity between the two directions is 2.0W / mK. The above-mentioned first direction P1 is the stacking arrangement direction of the layered structure, as shown in Figure 1, and is also the thickness direction of the layered sample. The second direction P2 is a direction perpendicular to the first direction P1, that is, along the direction of the first component layer or the second component layer, and is also along the cross-section of the layered sample.

[0064] Embodiment 2:

[0065] The general chemical formula of the La-Fe-Si based magnetic refrigeration composite material of this embodiment is: La 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z / Fe.

[0066] Scanning electron microscope was used to observe the La 0.84 Ce 0.36 Fe 13.68 Si 1.6 / Fe magnetic refrigeration composite microstructure, such as Figure 6 As shown in Figure 2, it can be seen that the sample consists of a first component layer and a second component layer, which are alternately stacked to form a unit. The first component layer is composed of a magnetocaloric phase, pores, and a non-magnetocaloric phase, in which the volume fraction of pores is about 11.3%. The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13Based on the above, the magnetocaloric phases are connected to form an integrated structure, and the volume fraction of the magnetocaloric phase is about 71.6%. The non-magnetocaloric phase is mainly α-(Fe, Si) (black area) and La-Ce-rich rare earth phase (white area), of which the volume fraction of α-(Fe, Si) phase is about 16.0%. It can be seen that the fine non-magnetocaloric phase is dispersed in the magnetocaloric phase. The second component layer is mainly α-(Fe, Si) with a thickness of about 0.2 mm. The La-Ce-rich layer has a volume fraction of about 16.0%. 0.84 Ce 0.36 Fe 13.68 Si 1.6 / Fe magnetic refrigeration composite material still maintains its intact shape after being filled with hydrogen.

[0067] In this embodiment, La 0.84 Ce 0.36 Fe 13.68 Si 1.6 The preparation method of the / Fe magnetic refrigeration composite material comprises the following steps in sequence:

[0068] 1) Press La 1.4 Ce 0.6 Fe 11 Si2 chemical formula ingredients are loaded into the crucible of a vacuum induction melting furnace, and high-purity argon gas is filled in after evacuation. When the temperature rises to the point where the raw materials are completely melted and the alloy melt is uniform, the alloy liquid is poured into a copper mold to form an alloy ingot;

[0069] 2) La prepared in step 1) 1.4 Ce 0.6 Fe 11 Si2 alloy ingots are mechanically crushed into powder and sieved;

[0070] 3) The La particles with a particle size of ≤38 μm sieved in step 2) are 1.4 Ce 0.6 Fe 11 Si2 alloy powder is used as an intermediate, and Fe powder and Si powder with particle size ≤38μm are prepared according to La 0.84 Ce 0.36 Fe 13.68 Si 1.6 The mixed powder is prepared according to the chemical formula, and the mixed powder is used as the first component layer, and the Fe powder with a particle size of ≤38μm as the second component layer is alternately poured into the mold in a nitrogen glove box and laid flat; wherein the mass of the mixed powder single layer is 0.8g, and the mass of the Fe powder single layer is 0.2g. The layered powder is pressed into a green body at room temperature and the pressure is 1GPa;

[0071] 4) La pressed in step 3) 0.84 Ce 0.36 Fe 13.68 Si 1.6 / Fe blank is placed in a quartz tube, evacuated, filled with argon, and sealed;

[0072] 5) Place the quartz tube containing the embryo in step 4) into an annealing furnace, heat to 1080°C, and anneal for 3 days to form a NaZn 13 La of magnetocaloric phase 0.84 Ce 0.36 Fe 13.68 Si 1.6 / Fe magnetic refrigeration composite material;

[0073] 6) La prepared in step 5) 0.84 Ce 0.36 Fe 13.68 Si 1.6 The La / Fe composite material was charged to saturation in a hydrogen atmosphere at 300°C and 0.2 MPa to obtain 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z / Fe magnetic refrigeration composite materials.

[0074] Physical performance test:

[0075] 1. Determination of La obtained in step 6) using superconducting quantum interference device vibrating sample magnetometer MPMS (SQUID) VSM 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z Thermomagnetic (MT) curves and isothermal magnetization (MH) curves of the Fe / Fe magnetic refrigeration composite material at different temperatures. Figure 7 It can be seen that the Curie temperature of the material is 315K. Figure 8 As shown in the figure, near the Curie temperature, the sample magnetization curve has an obvious inflection point, showing a first-order magnetic transition from paramagnetic to ferromagnetic state. According to Maxwell's relationship:

[0076]

[0077] The entropy change under different temperature and magnetic field changes is calculated from the isothermal magnetization curve. Fig. 9 It can be seen that low magnetic field changes can cause a large entropy change in the layered composite material. The maximum entropy changes under 0-1T and 0-2T magnetic field changes are 7.9J / kgK and 10.7J / kgK, respectively.

[0078] 2. Use laser thermal conductivity analyzer (LFA) to test the La obtained in step 5). 0.84 Ce 0.36 Fe 13.68 Si 1.6 / Fe layered composite material and the La obtained in step 6) 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z / Fe layered composite material thermal conductivity. At room temperature, the thermal conductivity of the sample in the first direction and the second direction before hydrogenation is 10.0W / mK and 16.2W / mK, and the difference between the two directions is 6.2W / mK; after hydrogenation, the thermal conductivity of the sample decreases slightly, and the thermal conductivity in the first direction and the second direction are 5.8W / mK and 9.9W / mK, respectively, and the difference between the two directions is 4.1W / mK, see Table 1.

[0079] Embodiment 3:

[0080] The general chemical formula of the La-Fe-Si based magnetic refrigeration material of this embodiment is: LaFe 11.6 Si 1.4 H z / Fe.

[0081] In this embodiment, LaFe 11.6 Si 1.4 H z The preparation method of the / Fe magnetic refrigeration composite material is different from the preparation method of the above-mentioned embodiment 1, and the only difference is that the annealing time in step 5) is different, specifically, the annealing time is 3 days.

[0082] The sample is composed of a first component layer and a second component layer, which are alternately stacked. The first component layer is composed of a magnetocaloric phase, pores and a non-magnetocaloric phase, in which the volume fraction of pores is about 11.2%. The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 Based on the compound, each magnetocaloric phase is connected to form an integrated structure, and the volume fraction of the magnetocaloric phase is about 73.9%. The non-magnetocaloric phase is mainly α-(Fe, Si) and La-Ce-rich rare earth phase, of which the volume fraction of α-(Fe, Si) phase is about 14.8%. The fine non-magnetocaloric phase is dispersed in the magnetocaloric phase. The second component layer is mainly α-(Fe, Si) with a thickness of about 0.3 mm. The layered structure of LaFe 11.6 Si 1.4 The / Fe magnetic refrigeration composite material still maintains its complete shape after being filled with hydrogen. The preparation process and physical properties are shown in Table 1.

[0083] Embodiment 4:

[0084] The general chemical formula of the La-Fe-Si based magnetic refrigeration material of this embodiment is: La 0.84 Ce 0.36 Fe 13.68 Si 1.6 Hz / Fe.

[0085] In this embodiment, La 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z The preparation method of the / Fe magnetic refrigeration composite material is compared with the preparation method of the above-mentioned Example 2, and the only difference is: the mass of the mixed powder single layer in step 3) and the mass of the Fe powder single layer are different. Specifically, the mass of the mixed powder single layer in step 3) is 1.6g, and the mass of the Fe powder single layer is 0.4g.

[0086] The sample is composed of a first component layer and a second component layer, which are alternately stacked. The first component layer is composed of a magnetocaloric phase, pores and a non-magnetocaloric phase, in which the volume fraction of pores is about 10.9%. The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 Based on the compound, each magnetocaloric phase is connected to form an integrated structure, and the volume fraction of the magnetocaloric phase is about 72.2%. The non-magnetocaloric phase is mainly α-(Fe, Si) and La-Ce-rich rare earth alloy, of which the volume fraction of α-(Fe, Si) phase is about 16.7%. The fine non-magnetocaloric phase is dispersed in the magnetocaloric phase. The second component layer is mainly α-(Fe, Si) with a thickness of about 0.4 mm. The La-Ce layered structure 0.84 Ce 0.36 Fe 13.68 Si 1.6 The / Fe magnetic refrigeration composite material still maintains its complete shape after being filled with hydrogen. The preparation process and physical properties are shown in Table 1.

[0087] Embodiment 5:

[0088] The general chemical formula of the La-Fe-Si based magnetic refrigeration material of this embodiment is: La 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z / Fe.

[0089] In this embodiment, La 0.84 Ce 0.36 Fe 13.68 Si 1.6 H z The preparation method of the / Fe magnetic refrigeration composite material is compared with the preparation method of the above-mentioned Example 2, and the only difference is: the mass of the mixed powder single layer in step 3) and the mass of the Fe powder single layer are different. Specifically, the mass of the mixed powder single layer in step 3) is 2.4g, and the mass of the Fe powder single layer is 0.6g.

[0090] The sample is composed of a first component layer and a second component layer, which are alternately stacked. The first component layer is composed of a magnetocaloric phase, pores and a non-magnetocaloric phase, in which the volume fraction of pores is about 12.8%. The magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 Based on the compound, each magnetocaloric phase is connected to form an integrated structure, and the volume fraction of the magnetocaloric phase is about 70.9%. The non-magnetocaloric phase is mainly α-(Fe, Si) and La-Ce-rich rare earth alloy, of which the volume fraction of α-(Fe, Si) phase is about 15.9%. Fine non-magnetocaloric phase is dispersed in the magnetocaloric phase. The second component layer is mainly α-(Fe, Si) with a thickness of about 0.6 mm. The layered structure of La 0.84 Ce 0.36 Fe 13.68 Si 1.6 The / Fe magnetic refrigeration composite material still maintains its complete shape after being filled with hydrogen. The preparation process and physical properties are shown in Table 1.

[0091] In the step 1) of the preparation method of the above embodiment, when preparing the ingredients, Ce can also be completely or partially replaced by one or two of Pr and Nd; in addition, when preparing the ingredients in step 1), La 1-x R x (Fe 1-a M a ) (13-y)b Si y A z Ingredients, R is selected from any one or a combination of two or more of Ce, Pr and Nd elements; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni and Al elements; A is selected from one or a combination of two or more of B and C elements; 0≤x≤0.5, 1≤y≤2, 0≤z≤0.5, 0≤a≤0.1, 0.5≤b≤1.5;

[0092] In addition, in step 3) of the preparation method of the above embodiment, Fe powder can also be replaced by Fe alloy powder, which is a binary or multi-element alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si elements. The pressing method is not limited to mold pressing, and the pressing temperature is not limited to room temperature, as long as the powder can be densified and formed.

[0093] In the above embodiment, in step 5), the composite material is cut into plates of different shapes for hydrogen charging, and the cross-sectional area thereof is 4 to 130 mm. 2 , thickness 1 to 2 mm. In addition, other sizes can be selected according to actual needs.

[0094] Table 1 Alloy composition, preparation process and physical properties of La-Fe-Si / Fe-based magnetic refrigeration composite materials

[0095]

Claims

1. A La-Fe-Si based magnetic refrigeration composite material, characterized in that: The La-Fe-Si based magnetic refrigeration composite material is a layered structure formed by alternately stacking and pressing a first component layer and a second component layer, wherein the first component layer comprises pores and a plurality of magnetocaloric phase units, and each magnetocaloric phase is interconnected to form an integral structure, and the second component layer comprises Fe or Fe alloy, and the magnetocaloric phase is NaZn 13 La(Fe,Si) type crystal structure 13 Base compound.

2. The La-Fe-Si based magnetic refrigeration composite material according to claim 1, characterized in that: The NaZn 13 La(Fe,Si) type crystal structure 13 The chemical formula of the base compound is: La 1-x R x (Fe 1-a M a ) 13-y Si y A z ; wherein, R is selected from any one or a combination of two or more of Ce, Pr and Nd elements; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni and Al elements; A is H; or, A is selected from one or a combination of two or more of B and C elements and H; x satisfies: 0≤x≤0.5, y satisfies: 1≤y≤2, z satisfies: 0.1≤z≤3, a satisfies: 0≤a≤0.

1.

3. The La-Fe-Si based magnetic refrigeration composite material according to claim 1, characterized in that: By mass percentage, the content e of the first component layer in the La-Fe-Si-based magnetic refrigeration composite material satisfies: 60 wt.% < e < 100 wt.%, and the content f of the second component layer in the La-Fe-Si-based magnetic refrigeration composite material satisfies: 0 < f < 40 wt.%.

4. The La-Fe-Si based magnetic refrigeration composite material according to claim 3, characterized in that: The first constituent layer further includes a non-magnetocaloric phase, and the first constituent layer is composed only of a La(Fe,Si) 13 base magnetocaloric phase, pores, and a non-magnetocaloric phase. By volume percentage, the content g of the magnetocaloric phase in the first constituent layer satisfies: 60 < g < 100 vol.%, the content h of the pores in the first constituent layer satisfies: 0 < h < 20 vol.%, and the content m of the non-magnetocaloric phase in the first constituent layer satisfies: 0 ≤ m < 20 vol.%.

5. The La-Fe-Si based magnetic refrigeration composite material according to claim 4, characterized in that: The Curie temperature range is 150K to 350K, and the entropy change value under a magnetic field change of 2T is not less than 8J / kgK.

6. The La-Fe-Si based magnetic refrigeration composite material according to claim 1, characterized in that: Denote the stacking direction of the layered structure as the first direction, and the direction perpendicular to the first direction as the second direction. The difference Δλ between the thermal conductivity λ1 of the La-Fe-Si-based magnetic refrigeration composite material along the first direction and the thermal conductivity λ2 along the second direction satisfies: Δλ ≥ 2W / mK.

7. The La-Fe-Si based magnetic refrigeration composite material according to any one of claims 1 to 6, characterized in that: The magnetic refrigeration composite material can be processed into a thickness of less than 2 mm and a cross-sectional area of ​​not less than 100 mm 2 plate material.

8. A method for preparing the La-Fe-Si based magnetic refrigeration composite material according to any one of claims 2 to 7, characterized in that: It successively includes the following steps: 1) According to the chemical formula La 1-x R x (Fe 1-a M a ) (13-y)b Si y A z Prepare raw materials; wherein R is selected from any one or a combination of two or more of Ce, Pr and Nd; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni and Al; A is selected from one or a combination of two or more of B and C; x satisfies: 0≤x≤0.5, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, b satisfies: 0.5≤b≤1.5; 2) Smelting the raw materials prepared in step 1) to form La 1-x R x (Fe 1-a M a ) (13-y)b Si y A z alloy; 3) La smelted in step 2) 1-x R x (Fe 1-a M a ) (13-y)b Si y A z The alloy is crushed into powder; 4) The La crushed in step 3) 1-x R x (Fe 1-a M a ) (13-y)b Si y A z Alloy powder is used as a first component layer, and is alternately laid flat with Fe or Fe alloy powder as a second component layer, and then pressed into a green body after being laid flat, wherein the Fe alloy powder is a binary or multi-component alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si elements; 5) annealing the compacted body in step 4) to obtain NaZn 13 Phase of type crystal structure; 6) Perform hydrogen charging treatment on the annealed green body in step 5) to form a La-Fe-Si-based room-temperature magnetic refrigeration composite material.

9. A method for preparing the La-Fe-Si based magnetic refrigeration composite material according to any one of claims 2 to 7, characterized in that: It successively includes the following steps: 1) According to R x Fe 13-y Si y The raw material is configured by chemical formula; wherein R is La; or, R is selected from any one or a combination of two or more of Ce, Pr, Nd and La, and x satisfies: 1≤x≤7, and y satisfies: 1≤y≤10; 2) Smelting the raw materials prepared in step 1) to form R x Fe 13-y Si y alloy, and then crushing the alloy into powder; 3) The R broken in step 2) x Fe 13-y Si y Alloy powder is used as an intermediate, and mixed with Fe powder and Si powder; or, mixed with Fe powder, Si powder and alloy powder according to R x (Fe 1-a M a ) (13-y)b Si y A z The mixed powder is prepared according to the chemical formula, wherein the alloy powder is a binary or multi-element alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si; R is La; or, R is selected from any one or a combination of two or more of Ce, Pr, and Nd elements and La; M is selected from any one or a combination of two or more of Cr, Mn, Co, Ni, and Al elements; A is selected from one or a combination of two of B and C, x satisfies: 0.8≤x≤1.2, y satisfies: 1≤y≤2, z satisfies: 0≤z≤0.5, a satisfies: 0≤a≤0.1, and b satisfies: 0.5≤b≤1.5; 4) Mix the R mixed in step 3) x (Fe 1-a M a ) (13-y)b Si y A z Alloy powder is used as a first component layer, and is alternately laid flat with Fe or Fe alloy powder as a second component layer, and then pressed into a green body after being laid flat, wherein the Fe alloy powder is a binary or multi-component alloy powder composed of Fe and Cr, Mn, Co, Ni, Al, B, C, and Si elements; 5) annealing the compacted body in step 4) to obtain NaZn 13 Phase of type crystal structure; 6) Perform hydrogen charging treatment on the annealed green body in step 5) to form a La-Fe-Si-based room-temperature magnetic refrigeration composite material.

Citation Information

Patent Citations

  • Article for magnetic heat exchange and methods for manufacturing an article for magnetic heat exchange

    CN101785072A

  • High-heat-conductivity rare-earth iron R-Fe-B magnet and preparing method thereof

    CN105118594A

  • LaFeSi based magnetic refrigeration composite material and preparation method and application thereof

    CN106906408A

  • High-strength La-Fe-Si-based magnetic refrigeration composite material and preparation method thereof

    CN116426809A

  • High-performance sintered neodymium-iron-boron permanent magnet material

    CN202948801U